Sustainable Ecotourism Infrastructure Spatial Planning (Site Plan) Integrated with the Mangrove Forest Ecosystem of Kuala Bubon, West Aceh, Indonesia - Ulhaq, Riza; Hasdanita, Fitry (LPPM Politeknik Aceh Selatan, 2025)
The issue of developing the Kuala Bubon mangrove forest in West Aceh as an ecotourism destination has emerged and is widely discussed in the public sphere, gaining much sympathy and support from the community, considering the forest’s high biodiversity of flora and fauna. However, ecotourism activities, if not properly managed, can pose a serious threat to the sustainability of the ecosystem, such as unplanned infrastructure development that damages the habitats of various flora and fauna. Therefore, ecotourism needs to be managed effectively through pre-ecotourism studies, particularly the design of sustainable infrastructure spatial planning. The goal of this research is to create a site plan for sustainable ecotourism infrastructure integrated with the mangrove ecosystem. This design ensures that the negative impacts of infrastructure development in ecotourism areas can be minimized through the application of sustainable strategies and practices. The stages of this research include: 1. Documenting the potential of natural resources as ecotourism attractions and ecological conditions, 2. Mapping spatial data on ecotourism potential using GIS applications, 3. Designing spatial infrastructure for supporting ecotourism by considering the needs of ecotourism and selecting areas that do not harm the habitats of flora and fauna using AutoCAD. The research was conducted in the Kuala Bubon mangrove forest, West Aceh, from July to August 2024. The results of the research identified six ecotourism potential points, including: 1) Ecotourism boat tours for flora and fauna observation, 2) Open-air camping ecotourism, 3) Fishing ecotourism, 4) Birdwatching ecotourism, 5) Recreational boating ecotourism, and 6) Sunset ecotourism with a coffee shop and heron watching. The spatial planning of ecotourism infrastructure becomes crucial as the foundation for sustainable ecotourism development.